The The Influence of Content Marketing, Influencers and Online Customer Reviews on Azarine Product Purchasing Decisions - Putri Waluyo, Millenia Pratama; Siswati, Endang (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
This type of research is quantitative research, the aim is to find out the extent of the influence of content marketing, influencers and online customer reviews on purchasing decisions for Azarine products. This study uses a type of quantitative research. The sample in this study was 98 respondents from the Faculty of Economics and Business, Bhayangkara University, Surabaya, using simple random sampling and purposive sampling. Using the t test, F test, and dominance with the help of SPSS and the results are content marketing, influencer, and online customer review variables simultaneously have a positive and significant effect on purchasing decisions . In the partial test (t test) it is known that the content marketing and influencer variables partially have a positive and significant effect on purchasing decisions Online customer reviews have a positive and insignificant effect. The influencer variable has the most dominant influence on purchasing decisions.